Small-area geographical variation in the prevalence of diabetes amongst Australian youth aged <20 years in 2021 - Ewan Cameron; Song Zhang; Aveni Haynes; Peter W. Gething (Australian and New Zealand Journal of Public Health)
Objectives: To characterise small-area geographical variation in the prevalence of diabetes in Australian youth. Methods: A combined statistical reconstruction and small-area estimation algorithm was applied to privacy-modulated data from the 2021 Australian Census. The census instrument and reconstruction accuracy was examined by comparisons against a hospital-based register and community register. Diabetes prevalence maps were created from the small-area estimates. Results: The median and interquartile range of estimated diabetes prevalence by small-area unit under our geospatial smoothing model were 1.76 [1.49–1.97] cases per 1000 population for those aged 0–14 years and 5.2 [4.4–5.9] cases per 1000 population for those aged 15–19 years old. Concentrations of elevated prevalence were identified in the vicinities of regional towns across South-East Queensland, regional New South Wales and regional Victoria. Across each of Australia’s five largest cities a gradient of decreasing youth diabetes prevalence from the outer suburbs to the urban centre was identified. Conclusion: Diabetes burden is systematically higher among rural and peri-urban resident youth in Australia compared with their urban counterparts. Implications for Public Health: Hotspots of prevalence in regional areas deserve attention from public health authorities.